Entrance skin dose of the thyroid gland area following exposure with different protocols of two panoramic and cone-beam computed tomography devices - Bardia Vadiati Saberi; Negar Khosravifard; Tahereh Mohtavipour; Farnoosh Khaksari; Sara Abbasi; Ataollah Shahmalakpoor (Wolters Kluwer Medknow Publications, 2019)
Background: Cone-beam computed tomography (CBCT) has gained considerable use, while radiation burden remains an important concern. Aims: This study aimed at determining the entrance skin dose of the thyroid gland area through exposure with the normal, soft, and hard modes of Vatech (Pax-i) panoramic device as well as different field of views (FOVs) of Vatech (Pax-i 3D) CBCT system. Materials and Methods: Dose measurements were performed on a head-and-neck phantom by an ion chamber dosimeter. Panoramic imaging was done in three normal, soft, and hard modes, each entailing woman, man, and child options. CBCT examinations were performed with various FOVs, each having normal, soft, and hard modes as well as woman, man, and child choices. Doses obtained from different protocols of the two imaging modalities were compared by paired t-test. Results: All FOVs in CBCT resulted in greater radiation dose than panoramic in each of the normal, soft, and hard exposure modes (P < 0.05). Dose amounts for the child and adult modes differed statistically significant in panoramic radiography as well as 80 × 80 and 90 × 120 FOVs of CBCT while in 50 × 50 maxilla, 50 × 50 mandible, 50 × 80 and 150 × 150 FOVs of CBCT, The child and adult doses were almost similar. Conclusions: Even the smallest size of FOV in the soft exposure mode which is expected to have the lowest amount of radiation among CBCT protocols resulted in greater thyroid exposure compared to panoramic examination. Furthermore, care should be taken in the selection of FOV, particularly for CBCT examinations of the children.